Cytostatic activity of the duplex drug linking 2′-deoxy-5-fluorouridine (5FdU) with 3′-C-ethynylcytidine (ECyd) against gastric adenocarcinoma cell lines - Weinreich, Frank-Jürgen; Schott, Sarah; Königsrainer, Ingmar; Zieker, Derek; Königsrainer, Alfred; Schott, Herbert (Investigational new drugs, 2011)
The cytostatic potential of the new duplex drug 2′-deoxy-5-fluorouridylyl-(5′➔5′)-3′-C-ethynylcytidine (5FdU(5′-5′)ECyd) was evaluated in comparison to those of 5-fluorouracil (5FU), 2′-deoxy-5-fluorourindine (5FdU), 3′-C-ethynylycytidine (ECyd), cisplatin, an equimolar mixture of 5FdU + ECyd and a three component-mixture of 0.75 μM epirubicin/0.90 μM cisplatin/3.0 μM 5FU (ECF) by incubation of the two human gastric adenocarcinoma cell lines 23132/87 and MKN-45. The molar composition of ECF was taken from data of a triple combination chemotherapy for human gastric cancer. Time and dose depending inhibition of cell growth was determinated using the CASY technology. A growth decrease of both cell lines from 100% to about 20% was observed by treatment with ECF over a course of 14 days. This result provided basis to estimate the cytostatic potential of all tested drugs and combinations thereof. Corresponding high activities in respect to ECF were achieved by incubation of 23132/87 cells with single drugs 49 μM 5FU, 10 μM cisplatin, 3.4 μM 5FdU, 0.65 μM ECyd, the mixture 0.32 μM 5FdU + 0.32 μM ECyd and 0.32 μM 5FdU(5′-5′)ECyd. The less sensitive MKN-45 cells require a 1.5-4 fold higher dose of the standard chemotherapeutics in order to achieve an equivalent cytostatic effect, in respect to the 23132/87 cell line,. However, the effect of the duplex drugs on MKN-45 cells was gained with a 5-fold lower dose than ECF. Due to its high cytostatic potential the duplex drug, which covalently links two active anticancer compounds, could be a new therapeutic alternative for chemotherapy in gastric cancer, currently treated with different combinations.
Online veröffentlicht: 2 July 2010
Gesehen am 16.12.2022